Exploring Spiritual Quotient (SQ) Implementation at the Faculty of Ushuluddin and Islamic Studies, UIN Sumatera Utara - Rambe, Uqbatul Khoir; Siregar, Husna Sari (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
Since the introduction of the concept of Spiritual Quotient (SQ) as a form of individual intelligence, numerous applications have been conducted to evaluate its effectiveness. SQ, which integrates reasoning, rationality, and inner intelligence, is a crucial factor in addressing and managing various phenomena. This study aims to explore the application of SQ within educational institutions, specifically within the Faculty of Ushuluddin and Islamic Studies (FUSI) at UIN Sumatera Utara (UIN SU). Employing a qualitative approach and utilizing interviews as the primary data source, this study reveals the necessity of implementing SQ in educational institutions through several mechanisms: non-political leadership, the appointment of competent individuals to campus positions, and the encouragement and motivation of students to develop their interests and talents to achieve their desired goals.